Teachers' beliefs about multilingualism in a course on translanguaging. (August 2020) - Gorter, Durk; Arocena, Eli
Abstract: In recent years new ideas about multilingualism and translanguaging have been widely debated in applied linguistics and sociolinguistics. A growing number of studies have investigated different aspects of translanguaging. Thus far only a few studies have focused on teachers' beliefs, attitudes or ideologies. In an earlier study, we found monolingual assumptions to be strong among teachers in the Basque Country and in Friesland. In the current study in-service teachers' beliefs about multilingualism and translanguaging are discussed in relation to the key role that teachers can play in changing educational practices. During a course of continuing professional development in-service teachers received training on multilingual approaches. Before, during and after the course data were collected on their beliefs about multilingualism and translanguaging. The outcomes reveal some important changes in the teachers' beliefs about separating languages, mixing languages and languages supporting each other and the application of those beliefs in the classroom. The complex relationship between professional development and changes in teachers' beliefs and practices is placed in a broader context of multilingual approaches to teaching.